REGISTRATION-ANALYTICAL MAINTENANCE OF RECEIVABLES IN THE AGRICULTURAL ENTERPRISES - Bondarchuk , N.V.; Vasilyeva , L.M. (The actual problems of regional economy development, 2016)
The article is devoted to the research of the registration-analytical maintenance of receivables in the agricultural enterprises. The purpose of this article is comprehensive research of theoretical and methodical positions for improving the registration-analytical maintenance of receivables in the agricultural enterprises. Definitely agricultural enterprises have to constantly monitor of the availability and repayment the receivable. Such the permanent control monitoring of receivables allows not only affectively distribute financial flows, but and successfully predict major changes, avoid a lot of problems and raise the level of competitiveness in today's market. It was found that an amount of receivables of organizations is influenced by a number of factors, namely: quality analysis of receivables and the consistency in the use of its results, customer payment discipline and the general economic situation of the branches to which they relate, the settlement system which is used in the enterprise, the conditions of contracts with contracting parties; the conditions of settlements with buyers and customers and other. The documents which kept the record of the accounts receivable have been considered. It is ascertained, that modern accounting and analytical system of accounts receivable does not always provide full, unbiased account information for the analysis of receivables agricultural enterprises. In order to ensure the timeliness and completeness of the records existing receivables suggested to agricultural enterprises use the analytical register «Analytical card of account contracts». JEL: M41